VIDEO CONTENT FOR THE BLIND PEOPLE: METHOD AUDIODESCRIPTION - Demchuk, A. B. (Radio Electronics, Computer Science, Control, 2014)
The problem of video access of people with total or partial loss of vision is studied. The typhlocomment as a method for blind adaptation of video content is described. When researching the problem of access of weak-sight people to the video content, it is required to understand that more than a most part of the information is provided to the viewer in the form of an image. The blind people hear all words of actors, sounds of the environment, processes at the screen, but it is difficult for them to identify the person to whom the specific words belong, what happens with heroes at the very specific moment, what is depicted in the given scene, it is difficult for them to understand reaction of actors, which the latter often express with the help of movements or mimics. Typhlocomments to video content for blind people are one of the real steps towards solution of the problem of limitation of access to such content.